Major developments in conulariid research: problems of interpretation and future perspectives - de Moraes Leme, Juliana; Guimaraes Simoes, Marcello [UNESP]; Coelho Rodrigues, Sabrina [UNESP]; Van Iten, Heyo; Carlos Marques, Antonio (Asociacion Paleontologica Argentina, 2008)
Renewed interest in conulariids has resulted in clarification of problems in the paleobiology of this group. Discoveries of skeletal structures and specimens preserved in situ, coupled with cladistic analyses, have led to a revival of Kiderlen's (1937) hypothesis that conulariids were polypoid scyphozoans or a sister taxon of this class. Until 1979, research on conulariids centered on the description of new species and on the erection of subgroups using phenetic approaches. Few papers addressed the paleobiology and phylogenetic affinities of conulariids, and none employed cladistics. In contrast, the 1980's saw the publication of major papers on the paleoecology of conulariids, and during this decade the hypothesis that conulariids were benthic organisms was corroborated. Also, new ideas concerning the affinities of conulariids, including the proposal that conulariids represent an extinct phylum, were presented. During the 1990's, the problem of conulariid affinities was widely debated, with authors advocating either that conularfids represent a separate phylum or that they were cnidarians. Near the close of that decade, certain advocates of a cnidarian affinity argued that conulariids were most closely related to Cniclaria. Taphonomic evidence indicates that conulariids were benthic animals originally oriented with their aperture opening upward and that they attached to or were embedded in hard and soft substrates. To understand unresolved problems we recorm-nend that (1) conulariid specialists develop a standard morphological nomenclature based on rigorous definitions; and (2) studies on conulariid paleoecology be carried out using a sequence stratigraphy approach.
Keywords: Conulariids; Cnidaria; Scyphozoa; systematics; paleoecology; Taphonomy